INOVASI PRODUK UMKM BERBASIS BAHAN LOKAL DI GLINGSERAN WRINGIN BONDOWOSO - Miftahus Salam; Moh. Irmawan Jauhari; Siti Aisyatul Arifah (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
This community service activity aims to strengthen and innovate UMKM in Glingseran Village, Bondowoso. The method used is ABCD with a focus on developing assets in the Glingseran community. The results of the community service stated that the development and innovation carried out by the team in community service activities in Glingseran Village, Bondowoso were able to encourage residents to review the need for fish baskets whether they would always depend on apus bamboo or try other materials that were easier and cheaper. Given that the availability of bamboo in Glingseran Village is running low and bamboo trees are needed to maintain areas with high soil water content. Innovation in sweet corn drink products can be done and made. However, the team and the community need to mature the concept so that the drinks sold have good competitiveness in terms of price and packaging according to current needs.